Ecotourism Content Resonance on TripAdvisor: A Netnographic Study of Penglipuran and Tenganan Villages - I Made Widiantara; Dwi Cahaya Putra Kadek; Lianda Ayu Puspita Ni Putu; Oka Wisnawa I Putu; Sedana Wibawa Yasa Gede; Upayana Wiguna Eka Saputra (UPT Publikasi Ilmiah UNISBA, 2026)
Village-based ecotourism in Bali, exemplified by Penglipuran and Tenganan Aga, blends environmental stewardship with living culture. This study aims to analyze the resonance of ecotourism content from traveler reviews on TripAdvisor to (1) assess alignment between promoted ecotourism values and visitors' lived experiences, (2) examine content patterns reflecting sustainable tourism practices, and (3) formulate strategic recommendations for digital ecotourism communication. Using netnography, we collected and cleaned 946 reviews (2015–2025) and applied thematic and sentiment analysis, triangulated with document analysis (promotional materials), in-depth interviews with village managers, and participant observation during field visits. Most reviews are positive, highlighting authentic culture and cleanliness. Word clouds and K-Means clustering reveal dominant themes: traditional architecture, community life, environmental upkeep, alongside minor critiques of commercialization and crowding. Hierarchical charts show different emphases: Penglipuran leads on environmental conservation, while Tenganan centers on cultural preservation and community economy. A connection map shows how culture, environment, and the local economy interrelate to shape experience. Sentiment analysis confirms a valence of >90% positive/neutral, with strong affective engagement toward sustainability initiatives. We conclude that user-generated content mirrors the success of both villages in delivering authentic ecotourism, while underscoring the need to manage overtourism (Penglipuran) and balance authenticity with commerce (Tenganan). Strategic recommendations are offered for sustaining digital communication congruent with on-site practice. Findings advance digital tourism communication theory, particularly e-WOM dynamics in community-based ecotourism, with practical implications for destination branding and sustainable tourism management.